Rearranging the Village Head Election Justice System Based on the Electoral Justice System and Restorative Justice - Arjuna Al Ichsan Siregar; Fandi Ahmad F; Indra Firmansyah (Universitas Medan Area, 2022)
The implementation of the Village Head Election (Pemilihan Kepala Desa) still leaves some problems. This study aims to analyze and describe the implementation of honest and fair principles based on indicators of the electoral justice system in the implementation of village head elections in Sleman Regency in particular and Indonesia in general. This study also aims to describe a model of the electoral justice system that can be developed in the upcoming Pemilihan Kepala Desa to resolve law enforcement issues in the Pemilihan Kepala Desa, one of which is through the application of a restorative justice model. This study uses empirical legal research methods with primary and secondary data sources. Primary data sources were obtained from the results of research in the field through an interview process with 20 key informants in the implementation of the Pemilihan Kepala Desa in Sleman Regency in 2021 spread over 9 (nine) villages. The secondary data sources used consist of primary legal materials and secondary legal materials obtained through literature study. The data analysis technique is qualitative data analysis through statutory and conceptual approaches. The results showed that the Pemilihan Kepala Desa in Sleman Regency in particular and Indonesia, in general, had not been held honestly and fairly. It is necessary to reorganize the Pemilihan Kepala Desa rules through an electoral justice system model approach, especially for normative design indicators and performance indicators of the Pemilihan Kepala Desa system. The application of restorative justice can strengthen efforts to enforce the Pemilihan Kepala Desa law in the future.